(untitled) (Molecular Medicine Communications, 2023)
In this issue Yusuf and colleagues investigated the association of association of fat, mass and obesity (FTO) gene polymorphism with diabetes and prediabetes in Pakistani population, Mannan and colleagues did a variant analysis of FOXE1 gene in non-syndromic cleft lip and palate in Peshawar, Pakistan, Zaib et al determined the frequency of p53 mutations and Epstein-Barr virus in Pakistani gastric cancer patients and investigated their association with the tumor grade, Rehman and her colleagues made an analysis of comparative effectiveness & renoprotective effects of hypoglycemic drugs for type 2 diabetes mellitus, and Ain et al reviewed the sources and mechanisms of chemoresistance in hepatocellular carcinoma.